Concerning Unprotected Sex and Illicit Substance Use among Iranian University Students - Banafsheh MORADMAND-BADIE; Lillian MWANRI; Ali MIRZAZADEH; Saeedeh MOYEDI-NIA; Mehrnaz RASOULINEJAD; Colin MACDOUGALL (国际转化医学杂志（英文版）, 2020)
The university student population is the largest adolescent group in Iran. we aimed to measure the prevalence of sexual and illicit substance use risk behaviours among university students in Tehran, Iran. This study employed a quantitative method strategy to study Iranian university students. An anonymous quantitative survey was conducted using a self-administrated questionnaire. About 392/400 (98.0％) of invited students completed the survey with an average age of 21.98 (18-35), and 58.7％ male. Lifetime substance use was reported by 14.8％ of participants. The most commonly used substances were grass (11.0％), hallucinogens (4.1％), and cocaine (2.6％). Moreover, 36.7％ of participants reported sexual contacts within the last 12 months. Compared to females, more males reported condom use in last sexual contact (30.7％ vs. 10.0％, P < 0.005), and multiple sexual partners (40.6％ vs. 16.7％, P < 0.005). About, 34 (27.2％) participant reported sex with a sex worker or a person who had a multiple sexual partner. Group sex was reported by 5.1％ of participants. Illicit substance use and unprotected sex are considerably high among university students. More effective prevention programs accessible to them are needed to reduce their vulnerability to associated harms to such risk behaviours.